Neuroendocrine Carcinoma of Esophagus: A Case Series - Singh, Sunita; Dalal, Niti; Chhabra, Sonia; Sharma, Jatin; Sen, Rajeev (Archives of Clinical and Medical Case Reports, 2020)
Esophageal Neuroendocrine carcinoma (NECs) are rare and aggresive type of esophageal carcinoma with positive neuroendocrine markers. The esophageal NECs present most commonly with gastrointestinal symptoms such as dysphagia and/or abdominal discomfort. They have the potential for distant metastasis. In the present case series, all the patients present with symptoms of dysphagia and ulcerative growth pattern with positive neuroendocrine immunohistochemical markers. <gdiv></gdiv>